ICAM-1 and S100β plasma value in children with sepsis - Lisa Safira; Anton H Pudjiadi; Sukman Tulus Putra (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
ICAM-1 release during sepsis is perceived to be related to brain injury. Whereas S100β has been known as one of brain injury markers.To measure mean value of ICAM-1, S100β, to find correlation between ICAM-1 and Glasgow Coma Scale (GCS), between S100β and GCS, also ICAM-1 and S100β.Analytical cross sectional study in 34 sepsis children, measurement of ICAM-1 and S100β plasma levels within day 1 and 3 since diagnosis of sepsis.Median level of ICAM-1 day one 548,1 (158,6 – 1256,1) ng/mL and day three 596,5 (185,5 – 1264,5) ng/mL (p=0,164). S100β median is significantly higher in severe than mild sepsis (p=0,008 dan p=0,021). On third day S100β was negatively related to GCS (r= - 0,452; p=0,003). The correlation observed between ICAM-1 and S100β on day one was r=0,146 (p=0,409) while on third day was r=0,184 (p=0,298).The prevalence of encephalopathy sepsis is 5.9%, Median ICAM-1 is higher on day three. Median of S100β is higher in severe than mild sepsis.There is no correlation between ICAM-1 and GCS in both sepsis. There was negative correlation between S100β and GCS on 3rd day of sepsis. No correlation between ICAM-1 and S100β on both measurement days.